Reduction - Abstraction - Analysis. Proceedings of the 31th International Ludwig Wittgenstein-Symposium in Kirchberg, 2008 - Hieke, Alexander (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2009)
Philosophers often have tried to either reduce "disagreeable" objects or concepts to (more) acceptable objects or concepts. Reduction is regarded attractive by those who subscribe to an ideal of ontological parsimony. But the topic is not just restricted to traditional metaphysics or ontology. In the philosophy of mathematics, abstraction principles, such as Hume's principle, have been suggested to support a reconstruction of mathematics by logical means only. In the philosophy of language and the philosophy of science, the logical analysis of language has long been regarded to be the dominating paradigm, and liberalized projects of logical reconstruction remain to be driving forces of modern philosophy.